Hubungan antara Waktu Tempuh terhadap Penyusutan Bobot Badan Sapi Bali dan Analisis Usaha di CV Lembusari Farm - Argonolo, Sony; Socheh, Mochamad; Haryoko, Imbang (ANGON: Journal of Animal Science and Technology, 2020)
Background. This study aims to study the relationship between different travel times with Bali cattle body weight loss and calculate the losses that occur due to Bali cattle body weight loss. Materials and methods. The material used is 75 Bali cattle with a range of 3 categories, namely 21-30 hours of travel time, 31-40 hours of travel time and 41-50 hours of travel time. This research method uses a survey method with stratified random sampling. Data analysis uses simple regression analysis. Results. Based on the results of research using correlation coefficient analysis shows that there is a real relationship between travel time to body weight loss of 0.311. The results of the study showed a correlation coefficient of travel time with a loss of 0.298. Conclusion. The addition of 1 hour travel time affects the weight loss of 0.418 kg and affects the loss of Rp. 17,252.00.